Seeking consent for research with indigenous communities: a systematic review. Issue 1 (December 2016) - Fitzpatrick, Emily; Martiniuk, Alexandra; D'Antoine, Heather; Oscar, June; Carter, Maureen; Elliott, Elizabeth
Abstract Background When conducting research with Indigenous populations consent should be sought from both individual participants and the local community. We aimed to search and summarise the literature about methods for seeking consent for research with Indigenous populations. Methods A systematic literature search was conducted for articles that describe or evaluate the process of seeking informed consent for research with Indigenous participants. Guidelines for ethical research and for seeking consent with Indigenous people are also included in our review. Results Of 1447 articles found 1391 were excluded (duplicates, irrelevant, not in English); 56 were relevant and included. Articles were categorised into original research that evaluated the consent process (n = 5) or publications detailing the process of seeking consent (n = 13) and guidelines for ethical research (n = 38). Guidelines were categorised into international (n = 8); national (n = 20) and state/regional/local guidelines (n = 10). In five studies based in Australia, Canada and The United States of America the consent process with Indigenous people was objectively evaluated. In 13 other studies interpreters, voice recording, videos, pictures, flipcharts and "plain language" forms were used to assist in seeking consent but these processes were not evaluated. Some Indigenous organisations provide examples of community-designed resources for seeking consent and describe methods of community engagement, but none are evaluated. International, national and local ethical guidelines stress the importance of upholding Indigenous values but fail to specify methods for engaging communities or obtaining individual consent. In the 'Grey literature' concerns about the consent process are identified but no solutions are offered. Conclusion Consultation with Indigenous communities is needed to determine how consent should be sought from the community and the individual, and how to evaluate this process.